ABOUT BLOCK STRUCTURE OF TERRITORY OF RA (Proceedings of the YSU C: Geological and Geographical Sciences, 2013)
In this work for the first time an attempt for collection and analyses of the results and data of researches on block structure of the earth crust of the territory of Armenia and adjacent regions are made. In the result of these researches unsolved problems were revealed and the ways of their solutions were offered. Concrete suggestions and ways of their solutions are brought. From these suggestions the main points are the definition of «block of the earth crust» conception, taking into account the depth structure of the earth crust up to 20 km and recommendations on ranking of blocks.